Analisis Penyusunan Landscape Pembangunan Kampus yang Berorientasi Green Campus Menggunakan Pendekatan Ekologi - Eko Sudaryanto; John Bimasri; Holidi Holidi (MAN 4 Kota Pekanbaru, 2026)
The green campus concept has become an important strategy for higher education institutions to support the Sustainable Development Goals (SDGs) through environmentally responsible campus planning. This study analyzed the preparation of a green campus-oriented landscape using a landscape ecology approach at the Universitas Musi Rawas campus development site, Musi Rawas Regency, Indonesia. The research was conducted from April to June 2026 following four stages: inventory, analysis, synthesis, and landscape concept development. Primary and secondary data were collected through field observations, interviews, and literature review, then analyzed qualitatively and quantitatively based on site characteristics. The findings indicate that the proposed landscape design integrates ecological principles with campus spatial planning by emphasizing green open spaces, water conservation, sustainable transportation, and energy-efficient infrastructure. The design enhances environmental quality, strengthens ecological resilience, improves microclimatic conditions, and supports the achievement of green campus indicators. Therefore, a landscape ecology-based approach provides an effective framework for sustainable campus development while contributing to the implementation of the Sustainable Development Goals (SDGs).